The aesthetic management of diastema closure treatment with indirect veneer using lithium disilicate: A case report - Kun Ismiyatin; Olivia Vivian Widjaja; Singgih Harseno; Ahmad Afif Dzulfiqar; Caeleb Fabrizio Sudarsono; Indira Moza Azzaria (Universitas Airlangga, 2022)
Background: Diastema is a space between two or more adjacent teeth that can interfere with the patient's aesthetic appearance. Various aesthetic treatments can be performed for diastema closure on anterior teeth, one of which is through the installation of veneers. The lithium disilicate ceramic material produces the thinnest veneer and has better properties than other materials, and is able to cover the anterior diastema with a fairly large width. Purpose: To describe the aesthetic procedure for closing the diastema of anterior teeth using indirect lithium disilicate ceramic veneer. Case(s): A 29-years-old male patient came with a complaint of dissatisfaction with her smile because of a gap between teeth 12 and 13. The teeth are in vital condition with normal overjet and overbite, and there are no systemic health problems. Case Management: The management of diastema closure on teeth 12 and 13 was carried out with indirect lithium disilicate veneer treatment. Lithium disilicate veneer has promising aesthetic results due to its enamel-like nature, minimally invasive because it requires minimal tooth reduction, good strength, and did not cause gingival irritation. As a result, this treatment could increase self-confidence of the patient. Conclusion: Diastema closure treatment using indirect lithium disilicate veneer is an effective treatment, gives satisfactory results and can increase the patient's confidence.